Taxonomic changes in Marchantiaceae, Corsiniaceae and Cleveaceae (Marchantiidae, Marchantiophyta) - Long, David G.; Forrest, Laura L.; Villarreal, Juan Carlos; Crandall-Stotler, Barbara J. (Phytotaxa, 2016)
Molecular phylogenetic studies of complex thalloid liverworts have resolved relationships that require taxonomic and nomenclatural changes. Since Bucegia and Preissia are deeply nested within Marchantia, species formerly placed in these genera are transferred to Marchantia as Marchantia romanica, comb. nov. and Marchantia quadrata, respectively, and placed in the new subgenus, Marchantia subg. Preissia, comb. et stat. nov. The families Exormothecaceae and Corsiniaceae are merged under the earlier name Corsiniaceae. The genus Stephensoniella Kashyap becomes a synonym of Exormotheca and its sole species S. brevipedunculata is transferred to Exormotheca, with the new combination Exormotheca brevipedunculata. In the Cleveaceae, the recent recognition of Clevea as distinct from Athalamia, necessitates the new combination Clevea nana to replace the name Clevea hyalina on the basis of nomenclatural priority.